Knowledge, Attitudes, and Practices towards Early Childhood Caries among Affluent Parents of Lahore: Knowledge, Attitudes, and Practices of Early Childhood Caries among Affluent Parents - Chaudhry, Ammara; Shakeel, Sadia; Shahid, Tayyaba Nayab; Anwar, Malik Adeel; Tariq, Khaloud; Rehman, Fatima; Azhar, Adrish (Pakistan Journal of Health Sciences, 2025)
Parents influence oral hygiene practices and children’s health behaviours as young ones lack the comprehension and dexterity to maintain oral health. Objectives: To evaluate the knowledge, attitudes, and practices about early childhood caries among affluent parents of Lahore. Methods: A cross-sectional study was conducted from August 2024 to October 2024 using non-probability sampling with 203 participants. Revalidated questionnaires inquiring about knowledge, attitude, and practice were distributed to parents with children under 5 years old, enrolled in affluent schools within the city. Frequency and percentage distributions were obtained for each qualitative variable and mean, and standard deviation were acquired for quantitative variables. The differences between genders were analyzed using chi-squared statistics. A p-value of less than 0.05 was considered statistically significant. Results: Among 203 participants, the majority were mothers 56.2% and the sample comprised of most male children in age group 3-5 years. Among the participants, more than half of the parents had graduated from university; some had graduated from high school. Only a few had completed their primary-level education. The overall mean knowledge score was 52.77 ± 21.59, whereas the mean score for attitude and practice was 61.24 ± 25.49 and 65.61 ± 26.66 respectively. Mothers had significantly greater overall knowledge (p=<0.001), better attitudes (p=0.164), and practices (p-value=0.112) towards early childhood caries as compared to fathers. Conclusions: It was concluded that although affluent parents of 5-year-old children had good knowledge regarding the Early Childhood Caries, their attitude and practices were still lacking in keeping up with the recommended standards.